2004
DOI: 10.1645/ge-283r
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the Ecology and Natural History of Paraergasilus Rylovi (Copepoda, Ergasilidae) Parasitic in Unionids of Finland

Abstract: The distribution of Paraergasilus rylovi in 17 populations of unionids was investigated. In 1 unionid population, the parasite was studied regarding host age, size, sex, and the reproductive period (occurrence of egg sacs). Results from pooled material from the years 1987--1989 and 1996 (southern Finland, 11 populations) indicated that Anodonta piscinalis (n = 1,359) is the main host (total mean prevalence 71% and intensity +/-SE of infection 16.4+/-0.6). Pseudanodonta complanata (n = 106) was infected occasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…We found that P. rylovi was better adapted to its local host population in a reciprocal transplant experiment (Saarinen and Taskinen, 2005 b). Our field observations (Saarinen and Taskinen, 2004) and experimental results (Saarinen and Taskinen, 2005 b) indicated clear habitat-dependence in abundance of P. rylovi, probably due to variation in exposure rate in different habitats.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…We found that P. rylovi was better adapted to its local host population in a reciprocal transplant experiment (Saarinen and Taskinen, 2005 b). Our field observations (Saarinen and Taskinen, 2004) and experimental results (Saarinen and Taskinen, 2005 b) indicated clear habitat-dependence in abundance of P. rylovi, probably due to variation in exposure rate in different habitats.…”
Section: Introductionsupporting
confidence: 59%
“…Clams were allowed to take a new burrowing position freely and to become infected naturally by P. rylovi. The reproductive period of P. rylovi is between June and August (Saarinen and Taskinen, 2004), and new infections are established in August (Saarinen and Taskinen, 2005 a). After 17 days, on 29 August 2005, burrowing depths were marked by a diver as described above and the clams collected and transported to the laboratory where they were examined and measured.…”
Section: Experimental Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Ergasilid parasites of fishes feed on gill tissues and blood, and may cause deformation or necrosis of the gill filaments (Bauer, Musselius & Strelkov, 1973). According to Saarinen & Taskinen (2004) the parasite was specific to A. piscinalis in the present study areas, and the annual reproductive period of the parasite was between June and August.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 70%
“…The parasite, an ergasilid copepod Paraergasilus rylovi Markewitsch (sensu Chernysheva & Purasjoki, 1991), has been observed only in north-east Europe, in gills of A. piscinalis (Chernysheva & Purasjoki, 1991 ;Saarinen & Taskinen, 2004). Ergasilid parasites of fishes feed on gill tissues and blood, and may cause deformation or necrosis of the gill filaments (Bauer, Musselius & Strelkov, 1973).…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%